1991
DOI: 10.1097/00004032-199103000-00001
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Transuranium Registry Report on the 239Pu Distribution in a Human Body

Abstract: The distribution of 239Pu in a human whole body is reported. The body contained 246 Bq of 239Pu of which 130 Bq (52.8%) was found in the lungs and associated lymph nodes. Of the remaining 116 Bq (47.2%) that constituted the systemic deposition, 51.2 Bq (44%) were in the skeleton, 48.6 Bq (42%) in the liver, and the remainder (14%) in the rest of the body exclusive of the lungs and associated lymph nodes. An unexpectedly high concentration was observed in the pituitary. The systemic distribution of Pu in this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The ICRP30 compartmental model for Class Y aerosols with an activity median aerodynamic diameter (AMAD) of 1 (jm is shown in Table 1, and the metabolic model for Th in body organs is shown in Table 2. ICRP30 pointed out the need for more metabolic data to reduce the uncertainties in estimates of committed dose equivalent, and Kathren (1988) has reported apparent discrepancies between metabolic models and measurements of long-lived actinide nuclides in humans. In a recent paper on the distribution of 239 Pu in a human subject, Mclnroy et al (1991) reported somewhat higher than predicted concentrations of Pu in soft tissues but rather good agreement with ICRP30 for the relative amounts in the skeleton and liver. Kathren (1988) emphasized that model predictions should be tested by comparison with actual measurements in human tissues after death, and this has already been done to some extent by studies of environmental Th in humans.…”
Section: Introductionmentioning
confidence: 68%
“…The ICRP30 compartmental model for Class Y aerosols with an activity median aerodynamic diameter (AMAD) of 1 (jm is shown in Table 1, and the metabolic model for Th in body organs is shown in Table 2. ICRP30 pointed out the need for more metabolic data to reduce the uncertainties in estimates of committed dose equivalent, and Kathren (1988) has reported apparent discrepancies between metabolic models and measurements of long-lived actinide nuclides in humans. In a recent paper on the distribution of 239 Pu in a human subject, Mclnroy et al (1991) reported somewhat higher than predicted concentrations of Pu in soft tissues but rather good agreement with ICRP30 for the relative amounts in the skeleton and liver. Kathren (1988) emphasized that model predictions should be tested by comparison with actual measurements in human tissues after death, and this has already been done to some extent by studies of environmental Th in humans.…”
Section: Introductionmentioning
confidence: 68%
“…Tissue samples collected at autopsy were analyzed for 238 Pu, 239+240 Pu, and 241 Am. Sample collection, dissection, and radiochemical analysis were described elsewhere (McInroy et al 1985; Moody et al 1998). Briefly, the tissue samples were dried at 120 °C, wet-ashed with the nitric acid and hydrogen peroxide mixture, and dry-ashed at 450 °C.…”
Section: Methodsmentioning
confidence: 99%
“…McInroy et al (38) have reported a whole-body distribution of 239Pu in an occupationally exposed worker. The worker was involved in operations with plutonium exposure from 1945 to 1982, approximately 10.5 months before his death.…”
Section: Dosimetrymentioning
confidence: 99%